2001
DOI: 10.1046/j.1365-2249.2001.01675.x
|View full text |Cite
|
Sign up to set email alerts
|

Delayed apoptosis of circulating neutrophils in Kawasaki disease

Abstract: SUMMARYCirculating polymorphonuclear neutrophils (PMNs) are known to increase in number and are functionally activated in the acute phase of Kawasaki disease (KD). In the present study, we investigated whether the apoptosis of PMNs is deregulated in KD. When the isolated PMNs were cultured in vitro, the proportions of spontaneous apoptotic PMNs (annexin V 1 cells and cells with fragmented DNA) were found to be significantly lower (P , 0´01) in the patients with KD (n 25) than in the patients with a bacterial i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 45 publications
2
42
0
Order By: Relevance
“…Delayed apoptosis of leukocytes is characteristic of acute KD and may contribute to pathogenesis [27]. Intravenous immunoglobulin (IVIg), standard therapy for KD, induces apoptosis of neutrophils in acute KD [28].…”
Section: Discussionmentioning
confidence: 99%
“…Delayed apoptosis of leukocytes is characteristic of acute KD and may contribute to pathogenesis [27]. Intravenous immunoglobulin (IVIg), standard therapy for KD, induces apoptosis of neutrophils in acute KD [28].…”
Section: Discussionmentioning
confidence: 99%
“…Elevated plasma levels of VEGF have been detected in acute KD and immunohistochemistry has demonstrated VEGF in coronary arteries, where it may mediate the prominent neovascularization seen in the arterial wall [43, 44]. Increased CEACAM1 expression has also been associated with delayed neutrophil apoptosis, which suggests that apoptosis may be an important pathway for decreasing inflammation in KD [18, 45, 46]. Therefore, measuring concentrations of the alternatively spliced variants of CEACAM1 in plasma may reveal it to be a useful biomarker in predicting IVIG-resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Since the prolonged survival of activated neutrophils has autotoxic potential due to the release of proteases and ROS, neutrophil apoptosis may represent a suitable mechanism for resolving inflammation. We previously reported that the apoptosis of neutrophils is inhibited during the acute phase of KD, and that an increase in the number of peripheral neutrophils may be associated with the delayed apoptosis of neutrophils [33]. Furthermore, IVIG can promote apoptosis in activated neutrophils in vitro by an oxygen-dependent pathway via FcγRII and III [34].…”
Section: Delayed Apoptosis Of Circulating Neutrophils In Acute Kdmentioning
confidence: 98%